Development of reversed deep drawing without blank-holder for producing brass elliptical cup - Hassan, Ali; Aziz, Hani; Hussein, Ola (International Journal of Engineering and Technology, 2018)
A new technique â€œReverse Deep Drawing Processâ€ without blank holder was adopted, for the single stage to produce an elliptical cup through an elliptical die. In this process an elliptical-cup is produced by pushing an elliptical blank using a hollow elliptical punch through an elliptical die in a single stroke. FEM via ANSYS is used to analyze this process. The clearance ratio was varied to study its effect on some parameters of this process like load, stress, strain, thickness distributions. A die with clearance =1mm and blank thickness=1mm gave the best drawability in this technique and no wrinkling observed on the product but it has minimum earring. Several attempted have been done to get the shape and dimensions of the blank, the major axis (a) =85mm & the minor axis (b) =65 mm was the better blank for this process to produce elliptical cup of major axis is twice minor axis. Good agreements are evident between the experimental and finite element results; the discrepancy is 4.0797% for load-extension and 0.852% for the wall thickness in minor axis and 1.145% in major axis.